Measurement of contagion in banks' equity prices - Reint E. Gropp; Gerard Moerman (European Central Bank (ECB), 2003)
This paper uses the co-incidence of extreme shocks to banks' risk to examine within country and across country contagion among large EU banks. Banks' risk is measured by the first difference of weekly distances to default and abnormal returns. Using Monte Carlo simulations, the paper examines whether the observed frequency of large shocks experienced by two or more banks simultaneously is consistent with the assumption of a multivariate normal or a student t distribution. Further, the paper proposes a simple metric, which is used to identify contagion from one bank to another and identify “systemically important” banks in the EU.
Keywords: G21; F36; G15; 330; banking; Contagion; Monte Carlo Simulations